Measurement of Temperature-Dependent Relaxation Oscillation Frequency and Linewidth Enhancement Factor of a 1550 nm VCSEL - Khan, Nadir Ali; Schires, Kevin; Hurtado, Antonio; Henning, Ian D.; Adams, Michael J. (IEEE journal of quantum electronics, 2013)
In this paper, we present detailed measurements of the temperature-dependent relaxation oscillation frequency and polarization resolved linewidth enhancement factor (α) of a 1550-nm vertical cavity surface emitting laser (VCSEL). The thermal effects on these parameters are investigated for a temperature range of -20°C to 60°C. Comparison is made between the experimental observations and theoretical predictions for similar VCSELs and with those different in operating wavelength and/or materials.